2017
DOI: 10.1055/s-0042-123711
|View full text |Cite
|
Sign up to set email alerts
|

Cromolyn Sodium Attenuates Paraquat-Induced Lung Injury by Modulation of Proinflammatory Cytokines

Abstract: The current study aimed to investigate the effects of Cromolyn Sodium (CS) on proinflammatory cytokines in Paraquat (PQ)-induced lung damage in rat. Animals were randomly divided into 5 groups. Group 1 and 2 received nebulized vehicle and CS (8 mg/kg) for 3 consecutive weeks, respectively. Group 3 was treated with single oral dose of PQ (40 mg/kg). Groups 4 and 5 were PQ groups which received nebulized CS (6 and 8 mg/kg/day, respectively) from 1 week before to 2 weeks after PQ administration. Finally, the anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Consistent with our previous findings [43], paraquat acted as a systemic stressor, as evidenced by its elevation of plasma corticosterone and IL-6, provocation of sickness behavior, and disturbances in nesting and motor behaviors. Indeed, we and others have shown that paraquat-induced increased pro-inflammatory cytokine levels in the brain, as well as in the lungs and in serum [19, 32, 4446]. We know that collectively these cytokines and corticosterone can act additively or even synergistically to provoke behavioral disturbances and neurochemical alterations and at high enough concentration can cause cellular death [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our previous findings [43], paraquat acted as a systemic stressor, as evidenced by its elevation of plasma corticosterone and IL-6, provocation of sickness behavior, and disturbances in nesting and motor behaviors. Indeed, we and others have shown that paraquat-induced increased pro-inflammatory cytokine levels in the brain, as well as in the lungs and in serum [19, 32, 4446]. We know that collectively these cytokines and corticosterone can act additively or even synergistically to provoke behavioral disturbances and neurochemical alterations and at high enough concentration can cause cellular death [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…The injection volume was 0.2 mL for each animal. At the end of study course, the mice were weighed and then anaesthetized with ketamine at 50 mg/kg and xylazine 10 mg/kg(13).…”
Section: Methodsmentioning
confidence: 99%
“…istopathological assessment was used at 200 x (scale bar = 100 μm) and 400 x (scale bar = 20 μm) magnification (Olympus BX51, Tokyo, Japan). Any changes in morphology such as infiltration of inflammatory cells, congestion, hemorrhage or hyperemia, necrosis were evaluated [21].…”
Section: Histopathological Reportmentioning
confidence: 99%